Keys for transforming the curriculum of the Chilean education system after the pandemic - Moreira-Arenas, Alexis (2022)
The curriculum in Chile has been under pressure in recent decades and, considering the implications of the pandemic, the pressure has spread and deepened. This situation has had repercussions for the curricular management of schools, where problems detected require a systemic analysis of their elements. In this article, through a review of national and international evidence, we reflect on curriculum management during the pandemic, focusing on primary school education. Tensions and challenges are addressed using the indicative performance standards currently in force in Chile as a reference. The analysis reflects the accumulation of administrative functions and responsibilities carried out by the management staff. Likewise, the analysis highlights an overloaded curriculum, lack of clarity in the use of non-instructional time, and problems in the understanding and treatment of evaluations and their link with learning objectives. We present three proposals to move forward: 1) educational policies aimed at greater curricular decentralization, based on a limited set of learning objectives at the national level and flexibility to incorporate objectives at the regional level; 2) professional development coherent with curricular design and implementation in regional teams; and 3) specific spaces for school principals to analyze pedagogical practices that allow for relevant curricular implementation.